Phase behavior of petroleum reservoir fluids. - Pedersen, K. S.; Christensen, Peter L.; Shaikh, Jawad Azeem (CRC Press, Taylor & Francis Group, 2015)
Developed in conjunction with several oil companies using experimental data for real reservoir fluids, Phase Behavior of Petroleum Reservoir Fluids introduces industry standard methods for modeling the phase behavior of petroleum reservoir fluids at different stages in the process. Keeping mathematics to a minimum, this book discusses sampling, characterization, compositional analyses, and equations of state used to simulate various pressure-volume-temperature (PVT) properties of reservoir fluids.
Previous edition: 2007.
Keywords: Petroleum reserves -- Mathematical models.; Petroleum -- Geology -- Mathematical models.; Phase rule and equilibrium.; Thermodynamic equilibrium.; Heavy oil.; Hydrocarbons.; elektronické knihy; electronic books